RGB IMAGE BINARY DECOMPOSITION BASED ARABIC AND ENGLISH TEXTS HIDING ALGORITHM WITH 16 CHARACTERS FORMING VIGENERE KEY - Huda Hussein Abed; Salim Muhsin Wadi; Aqeel Sajjad Shaeel (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The transfer of secret texts via channels requires a higher level of security to prevent any third party from revealing or extracting any information related to it. In this paper, a secure hiding algorithm for protecting the secret texts either Arabic or English based on RGB image binary decomposition with 16 characters forming the Vigenere key is proposed. The main feature of the proposed algorithm can be summarized as offering security without transferring any information relating to the secret texts with the stego image. The RGB image is scrambled by binary decomposition and reordered its bit plan. Then, the secret text either Arabic or English is encrypted using 16 characters of Vigenere key with a new method for forming this key based on primary and secondary diagonal pixels of the scrambled red channel. On the other hand, the ciphertext length is hidden in the corner pixels of the same scrambled red channel. The performance of the proposed steganographic scheme is evaluated using the elapsed times for its implementation, PSNR, and MSE while the security provided for the spatial domain pixels in the scrambled green and blue channels before hiding the ciphertext is evaluated using histogram analysis and the entropy value. The simulation results demonstrate the security that is provided for the secret texts during the transmission of the RGB stego image